Physical activity promotion apps for adolescents. Narrative review of key behavior change techniques and central features - Hugo Vieira Pereira; Diogo S. Teixeira; Malgorzata Slawinska; Paul Davis; Marcos López-Flores; Markus Nyström; Marlene N. Silva; António L. Palmeira; Lúcia Gomes (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Previous research has not explored features and behavior change techniques (BCTs) in physical activity (PA) promotion interventions among adolescents, including mobile health (mHealth) applications. Purpose: This study aims to conduct a narrative literature review of adolescent PA promotion apps, examining their theoretical foundations, key BCTs, primary features, and their influence on PA adherence and maintenance. Methods: The review includes peer-reviewed studies published from 2012 to December 2024, employing qualitative and quantitative methodologies. Included studies examined healthy adolescents, focusing on PA app features and their relationship to PA promotion. Results: A total of twenty-one studies were analyzed: ten reviews, eight qualitative studies, and three app quality assessments. Findings indicate that mHealth tools and wearable trackers yield variable impacts on PA engagement. Conclusion: Future research must adopt higher methodological standards. Comparative studies on PA interventions require caution due to limitations such as insufficient research, inadequate compliance assessment tools, potential biases, and the absence of randomized controlled trials. The inconsistent outcomes from current intervention studies highlight the necessity for developing PA programs guided by intervention mapping or the Behavior Change Wheel, emphasizing high-quality methodologies tailored to specific target demographics.